Determinar el proceso de venta de la empresa Mundoline para la elaboración de instructivo y procedimiento de trabajo. - Peña Baldeon, Luz Del Rocio (My University, 2018)
The research work presents the problematic about the process of sale of the company MundoLine, based on observations made and applying a methodology according to the study was investigated on the lack of an instruction or manual for the control and supervision of the procedure in the sale and the problems that the company currently presents, we proceeded to the identification of the most important aspects for the elaboration of the theoretical framework, described methods and techniques for the collection of information based on the flow diagrams to understand the internal processes of the organization, This helped to explain the results and be valid according to the current situation of the company, for this reason it is necessary to develop an instruction that benefits and identifies the procedures and the people who are responsible for their role The investigative work presents the problematic about the process of sale of the company MundoLine, which offers its clients services of internet provider and the sale of electronic devices, based on observations made to the various processes used by the organization to cover its commercial activities and applying a methodology according to the study was found the lack of a manual or manual for the control and supervision of the procedure in the sale and the problems currently presented by the company, has shown inadequate processes in the sale with conflicts between the employee staff product of the existence of duplicate operations and with little training in the participation of customer services, this leads to the creation of conflicts and causes the tasks to fail resulting in low economic performance and management, proceeded to the identification of most important aspects for the elaboration of the sea Theoretical, described methods and techniques for the collection of information, several flowcharts of the sales tasks were elaborated to understand the internal processes of the organization, this helped to explain the results with valid data and according to the current situation of the company, for this reason it is necessary to develop an instruction that benefits and identifies the procedures and people who are responsible for their role and thus the actions will have greater control and effectiveness.
El trabajo investigativo presenta la problemática sobre el proceso de venta de la empresa MundoLine, que ofrece a su clientela servicios de proveedor de internet y la venta de dispositivos electrónicos, basados en observaciones realizadas a los diversos procesos que emplea la organización para cubrir sus actividades comerciales y aplicando una metodología acorde al estudio se comprobó la falta de un instructivo de trabajo o manual para el control y supervisión del procedimiento en la venta y de los problemas que presenta actualmente la empresa, se ha evidenciado inadecuados procesos en la venta con conflictos entre el personal de empleados producto de la existencia de operaciones duplicados y con escasa capacitación en la participación de servicios al cliente, esto conlleva a la creación de conflictos y hace decaer las tareas produciendo un bajo rendimiento económico y de gestión, se procedió a la identificación de los aspectos más importantes para la elaboración del marco teórico, se describió métodos y técnicas para la recolección de información, se elaboró varios diagramas de flujo de las tareas de venta para entender los procesos internos de la organización, esto ayudó a la explicación de los resultados sea con datos valederos y acorde a la situación actual de la empresa, por esta razón es necesario la elaboración de un instructivo que beneficie e identifique los procedimientos y las personas que son responsables para su función y de esta manera las acciones tendrán un mayor control y eficacia.
Keywords: PROCESO DE VENTA; INSTRUCTIVO DE TRABAJO; EMPRESA